Regional Knowledge Management: Contrasting Skills in Science, Technology and Innovation Along the Atlantic Space - Teresa De Noronha Vaz (European Regional Science Association (ERSA), 2006)
This paper represents an effort to evaluate the current position and perspectives of science, technology and innovation in several Atlantic Regions. It is based on the results of a still running European research project (REGINA) that puts together Andaluzia, Algarve, Norte, Galicia, País Vasco, Bretagne, West Midlands and Border, Midland and Western. Not discussing the large spectrum of the goals of that project, this is an exercise to discuss the possibility of setting up a lasting partnership for regional knowledge management in the politically so important Atlantic space. Comprehending Spain, Portugal, France, United Kingdom and Ireland, this part of Europe also integrates regions lagging in terms of tacit and codified knowledge environments and, consequent innovative attitudes. Would they benefit of a better territorial development balance within the Atlantic space in case of a regional innovation system common strategy? And if so, which sectors are those to show greater skills for technological transfer within cooperative performances? Highlighting an interactive model for which knowledge creation is understood in a broad perspective and innovation implicitly demands more than a simply gathering of discoveries and inventions the theoretical framing accepts the adaptation and combination of existing forms of knowledge. This interactive and dynamic concept emphasises the external environment of the firms in addition to their internal knowledge creation capacity and refers a synthetic framework based on the concept of the learning process as a driver to redress stakeholders' attitudes and strategic choices. In such a context, the advantages that may result from institutional geographical proximity or similarity, specific knowledge diffusion and networking in coordination of common interests could build up advantages. In short, the specific construction of a territorial knowledge base and the consequent achievement of more sustainable regional development for a large part of the European Atlantic border are discussed in this practical case. Based on secondary data from the European Innovation Scoreboard, an outline over the regional innovation performances of the considered regions will be supplied. Also, based on primary data obtained near the institutional bodies of each region, an analysis of the existent governance structures is possible. The conclusion allows considerations related to the present context for the development of an Atlantic spatial development strategy.
Keywords: 330